2023
DOI: 10.1002/adhm.202203243
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Two‐Phase Emulsion Bioresin for Facile One‐Step 3D Microgel‐Based Bioprinting

Abstract: Microgel assembly as void-forming bioinks in 3D bioprinting has evidenced recent success with a highlighted scaffolding performance of these bottom-up biomaterial systems in supporting the viability and function of the laden cells. Here, a ternary-component aqueous emulsion is established as a one-step strategy to integrate the methacrylated gelatin (GelMA) microgel fabrication and assembly through vat photopolymerization in situ using digital light processing (DLP)-based bioprinting. The as-proposed aqueous e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…As expected, the ATPE hydrogels showed enhanced biocompatibility compared to the bulk hydrogels attributed to the macroporous structure that facilitates cell spreading and mass transfer. [7,16] The proliferation and the metabolic activity of cells in p_ATPE hy-drogels were significantly higher than that in the ATPE hydrogels, especially on day 3, indicating faster recovery of the cells (Figure 5a). To evaluate the cell viability post-bioprinting, we performed the live/dead staining on the bioprinted hydrogels, as displayed in Figure 5b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, the ATPE hydrogels showed enhanced biocompatibility compared to the bulk hydrogels attributed to the macroporous structure that facilitates cell spreading and mass transfer. [7,16] The proliferation and the metabolic activity of cells in p_ATPE hy-drogels were significantly higher than that in the ATPE hydrogels, especially on day 3, indicating faster recovery of the cells (Figure 5a). To evaluate the cell viability post-bioprinting, we performed the live/dead staining on the bioprinted hydrogels, as displayed in Figure 5b.…”
Section: Resultsmentioning
confidence: 99%
“…[15] Our previous study also demonstrated using a water-soluble non-ionic polysaccharide derivative as an emulgator to improve the emulsion stability by co-partitioning in both GelMA and dextran phases. [16] Another effective strategy is the Pickering emulsion method by applying biocompatible nanoparticles that settle on the interface and form a barrier to prevent droplet coalescence. [13,14] Pickering emulsion could not only improve the stability of the ATPE-based bioinks but also offer multifunctionality by specifically tailoring the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Our printed foams were compared with the literature reports for foams that were 3D printed by various technologies (Fig. 5(C)) 15,16,21–24,26,27,30–32,39,47–53 to construct the plot, we searched publications under the keywords “3D printing”, “foams” or/and “porous”, and evaluated only the papers that contained tensile measurements. It should be noted that most publications on photopolymerization-based printing of foams/porous materials result in stiff polymers 37,54 or ceramics 55–57 that cannot elongate and therefore tensile measurements were not reported for.…”
Section: Resultsmentioning
confidence: 99%
“…The printed auricular constructs have high elasticity, high printing accuracy, and low swelling ratio, which can mimic the microenvironment for cartilage regeneration. Wang et al established a one-step strategy to integrate the GelMA microgel fabrication and assembly through vat photopolymerization in situ using DLP bioprinting [ 132 ]. Although bioprinting is appealing for building tissue mimics, precise positioning control of mini-tissue blocks (i.e., spheroids) in 3D space remains challenging.…”
Section: Classification Of Microparticles For Generating Various Ink ...mentioning
confidence: 99%